Academic freedom, responsibility, and restrictions: Voices of university teachers in Iceland - Frímannsson, Guðmundur Heiðar; Ólafsdóttir, Anna; Geirsdóttir, Guðrún; Kristinsson, Sigurður; Bjarnadóttir, Valgerður S. (Stjórnsýslustofnun, 2022)
Academic freedom is essential to universities. The article discusses the nature and value of academic freedom and reports study results on how it is understood by university teachers in Iceland and what they see as threatening it. Two key aspects of academic freedom are identified: (a) free choice of topics and methods in research and teaching, and (b) a knowledge and integrity requirement. The article is based on data collected in two research projects, i.e. data from questionnaires and group interviews collected in the first project and interviews with individuals in the second project. The questionnaires were collected in 2011, the group interviews were conducted in 2014 and the interviews with individuals in 2019-2020. A total of 48 academic staff from three universities were interviewed, 26 females and 22 males. Participants were asked how they understood academic freedom and how it related to various aspects of their job as researchers and university teachers. The results show that university teachers in Iceland place great value on academic freedom understood as the freedom to choose topics and methods, primarily in research but also in teaching. Their understanding is that this freedom comes with requirements of knowledge, integrity, and peer-review, both in research and teaching. Participants perceive restricted academic freedom as a result of political and economic pressure, competition for limited funds, the institutional system for performance assessment, and limited avenues for publication. Concerns about limited-term hiring and silencing were not voiced. Results are consistent between all three data sources. Akademískt frelsi er órjúfanlegur þáttur háskólastarfs. Í greininni er rakið inntak og mikilvægi akademísks frelsis og sagt frá niðurstöðum rannsókna á skilningi íslenskra háskólakennara á því og ógnum þess. Tilgreindir eru tveir inntaksþættir, (a) frjálst val viðfangsefna og aðferða í rannsóknum og kennslu og (b) þekkingar- og heilindakrafa. Greinin byggir á gögnum úr þremur gagnasöfnum sem ...